2019
DOI: 10.1111/ijfs.14266
|View full text |Cite
|
Sign up to set email alerts
|

Thermally treated soya bean oleosomes: the changes in their stability and associated proteins

Abstract: Oleosomes are subcellular organelles present naturally in plant seeds for storing lipids. Oleosomes can be used in the preparation of various food products, such as creams, salad dressings, mayonnaise and emulsion. However, food products are always subjected to thermal processing, and therefore, the evaluation of the thermal stability of oleosomes is of great important. The present work aimed to understand the effect of soya bean oleosome-associated proteins (SOAPs) on the thermal stability of soya bean oleoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 43 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…Post pasteurization, the composition of the membrane proteins of the OBs obtained from the different crops varied (Fig 1). Based on previous reports, the membrane protein composition of soybean (Ding et al ., 2019), sunflower, peanut (Chen et al ., 2018; Zaaboul et al ., 2018), sesame and walnut (Yan & Zhou 2021) is shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Post pasteurization, the composition of the membrane proteins of the OBs obtained from the different crops varied (Fig 1). Based on previous reports, the membrane protein composition of soybean (Ding et al ., 2019), sunflower, peanut (Chen et al ., 2018; Zaaboul et al ., 2018), sesame and walnut (Yan & Zhou 2021) is shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…1c). The hydrophobic forces of the disulfide bonds and non‐disulfide covalent bonds between the proteins and fatty acids play an important role in the development of protein aggregation (Potes et al ., 2013; Ding et al ., 2019). In the reducing SDS‐PAGE, protein aggregation may be caused by the non‐disulfide bonds only as the disulfide linkages of the proteins decreased with the addition of β‐mercaptoethanol and SDS.…”
Section: Resultsmentioning
confidence: 99%
“…The protein content of soybean flour was determined by the Dumas nitrogen quantification method, and the protein content of the SOBs was determined according to a method previously reported. 20 Freeze-dried SOB samples (2 g) were dispersed in a 4% (w/v) SDS solution in DI water. The mixture was spun for 1 min and then centrifuged at 12 000g for 40 min.…”
Section: Papermentioning
confidence: 99%
“…In contrast, several studies have reported the relatively high heat stability of oleosomes. Crude extracts of soy and maize oleosomes showed high stability to coalescence even at temperatures as high as 90°C and for durations from 15 min to 1 h (Nikiforidis et al, 2011 ; Ding et al, 2020 ). However, the heat-treated oleosomes had a high degree of aggregation because of protein–protein interactions between non-oleosome proteins that adhered to the oleosomes (Nikiforidis et al, 2011 ; Chen et al, 2012 ).…”
Section: Nature-assembled Structures In Plantsmentioning
confidence: 99%
“…However, the heat-treated oleosomes had a high degree of aggregation because of protein–protein interactions between non-oleosome proteins that adhered to the oleosomes (Nikiforidis et al, 2011 ; Chen et al, 2012 ). More extensive heat treatment at 100°C for 15 min caused extensive coalescence in soy oleosomes, suggesting significant structural changes in the interfacial layer at these temperatures (Ding et al, 2020 ). Thermal treatment tended to improve the oxidative stability of oleosomes, which was attributed to the denaturation of lipolytic enzymes (Chen et al, 2012 ; De Chirico et al, 2020 ).…”
Section: Nature-assembled Structures In Plantsmentioning
confidence: 99%